Touching Allah in Ahmadiyah at the Mubarak Glugur Darat I Mosque, East Medan District, Medan City - Suwandi Mikail Siagian; Zulkarnaen Zulkarnaen; Heru Syahputra (Civiliza Publishing, Indonesia., 2026)
Tawheed occupies a fundamental position in the construction of Islamic teachings because it is the main basis for the relationship between humans, beliefs, and religious authorities, but the dynamics of the development of modern religious movements have given birth to various theological interpretations that give rise to contestation in the midst of Islamic orthodoxy, including in the Ahmadiyya community. This paper aims to analyze the construction of the concept of appreciating Allah in the Ahmadiyya understanding in the Mubarak Glugur Darat I Mosque, East Medan District, Medan City, the basis of the theological interpretation used, the manifestation of the teachings in the religious practice of the congregation, as well as the forms of theological contestation that arise in their relationship with the surrounding Muslim community. This study uses a qualitative method with phenomenological and social theology approaches. Data was obtained through participatory observation, in-depth interviews with administrators and worshippers, and documentation, then analyzed interpretively. The findings show that the Ahmadiyya monotheistic construction is built through an emphasis on the oneness of Allah which is understood normatively through the Qur'an, hadith, and the internal authority of the congregation's interpretation, with an orientation on the purification of worship, spiritual loyalty, and the moral discipline of the congregation. This pattern of interpretation shows a reinterpretation of the concept of prophethood, the authority of revelation, and the position of spiritual leaders which are the main points of difference with the mainstream of Islam. In religious practice, the congregation displays a religious pattern that is structured, exclusive in internal coaching, but adaptive in social relations. On the other hand, the theological construction presents multi-layered dynamics of legitimacy and rejection, ranging from the stigma of deviation from the faith, the restriction of the space for religious expression, to the negotiation of Islamic identity in the local public space.